Symmetric Cryptography Modification Using Diffie Hellman On RDBMS - Niko Surya Atmaja (Yayasan Sinergi Multidimensi Kreatif, 2024)
One of the most widely used and freely available RDBMS is MySQL. MySQL users generally do not care about the confidentiality of the contents stored in MySQL. The application of data confidentiality in MySQL generally only uses a username and password to protect MySQL but not its contents. Therefore, it is necessary to apply the confidentiality of the data content in MySQL so that thieves cannot obtain information from the data contained in MySQL by converting the contents of the text stored in MySQL into secret text. This research uses one of the symmetric cryptography, namely vigenere cipher to keep the text stored in MySQL secret. The disadvantage of symmetric cryptography compared to asymmetric is the same encryption and decryption keys. Therefore, this research modifies the key in symmetric cryptography using Diffie Hellman so that the key used becomes asymmetric. So that with symmetric cryptography using Diffie Hellman on the contents of the data stored in MySQL, MySQl gets better confidentiality of its data content